A contribuição do patrimônio arquitetônico na qualidade visual do entorno da praça Pinheiro Machado- Santo Ângelo/RS - Silva, Fiama Piltz da (2020)
This research delas with the contribution that the architectural heritage exerts on the landscape around Square Pinheiro Machado in Santo Ângelo-RS from the Environmental Perception área. The study was carried out using qualitative and quantitative methods in four stages of investigation. The first stage had the purpose of gathering subsidies to characterize the study area. The second and third stages were aimed at testing the hypotheses of this research, and in the second phase the tool used was the development of photographic workshops, while in the third phase the application of na open questionnaire was adopted. Finally, the fourth stage was aimed at developing a photographic exhibition based on the contente obtained through the previous stages, with the objective of promoting heritage education activities in the local Community. The information obtained by the photographic workshops was analyzed qualitatively, while the data resulting from the questionnaire of open questions were analyzed by frequency and similarity, tabulating the answers to obtain quantitative sentences. The results made it possible to understand the importance of historical architecture in the composition of the urban landscape of the case studied, as well as the existing relationships between their formal and symbolic characteristics, through the individual analysis of the historical buildings are those that make up the inventory of real estate in Santo Ângelo-RS, just as a way of delimiting the study sample, however, it is believed that the entire construction has historical value, since they are all the physical and spatial translation of the legacy of man on earth. At the end, it can be concluded that the built cultural heritage contributes qualitatively to the studied urban landscape, however its physical characteristics such as: state of conservation, architectural forms, colors and visual communication are directly related to the way the community perceives and atributes values to this space.